Magnetic transitions and electrical transport in Bi-doped lanthanum strontium manganites - Ahmed, A.M.; Mohamed, H.F.; Šoka, Martin (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The temperature dependence of the electrical resistivity ρ, thermoelectric power S and the magnetic susceptibility χ of La0.7–xBixSr0.3MnO3 (x = 0.05, 0.10, and 0.15 at.%) manganites were investigated. La0.7–xBixSr0.3MnO3 crystallizes in a single phase rhombohedral structure with parasitic phase inclusions. With increasing Bi concentration, a systematic decrease in the ferromagnetic transition temperature (TC), the metal–semiconducting transition temperature (Tms1) and also the values of activation energies Eρ and ES from ρ(T) and S(T) were observed. On the other hand, in the high-temperature (T > Tms) paramagnetic semiconductor regime, the adiabatic small polaron hopping model fit well, thereby indicating that polaron hopping might be responsible for the conduction mechanism. In addition, the thermoelectric power data at low temperatures were analyzed by considering both the magnon and the phonon drag concept, while the high-temperature data were confirmed a small polaron hopping conduction mechanism.